Clinical Simulation Center of the Universidad Antonio Nariño: innovation and excellence in the training of health professionals. (VITAL, 2025)
The Clinical Simulation Center at UAN trains students with advanced technology in a safe environment, developing technical, interpersonal and leadership skills to face clinical challenges.
Keywords: Medical education; Technology; Clinical simulation